2019
DOI: 10.1155/2019/4520645
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prostate Cancer Cells by 4,5-Dicaffeoylquinic Acid through Cell Cycle Arrest

Abstract: Prostate cancer is a major cause of cancer-related mortality in men. Even though current therapeutic management has contributed to reducing mortality, additional intervention strategies are warranted to further improve the outcomes. To this end, we have investigated the efficacy of dicaffeoylquinic acids, ingredients in Yerba Mate (Ilex paraguariensis), an evergreen cultivated in South America, the leaves of which are used to prepare a tea/coffee-like drink. Of the various analogs tested, 4,5-dicaffeoylquinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…Among the differentially perturbed B. pilosa metabolites were HCA derivatives, identified as significant ions in response to treatment with either elicitor. In previous studies, these groups of secondary metabolites were reported to have various health benefits such as anti-cancer properties [ 50 ], HIV-integrase inhibition by 3,5-di-caffeoylquinic acid [ 51 ] and chicoric acid [ 52 ] and anti-diabetic properties [ 53 , 54 ]. In this study, the di-caffeoylquinic acids, the 4,5-, 3,4- and 3,5- geometric isomers exhibited similar distribution profiles, prominent in the MeJA_12 and the MeSA_24 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the differentially perturbed B. pilosa metabolites were HCA derivatives, identified as significant ions in response to treatment with either elicitor. In previous studies, these groups of secondary metabolites were reported to have various health benefits such as anti-cancer properties [ 50 ], HIV-integrase inhibition by 3,5-di-caffeoylquinic acid [ 51 ] and chicoric acid [ 52 ] and anti-diabetic properties [ 53 , 54 ]. In this study, the di-caffeoylquinic acids, the 4,5-, 3,4- and 3,5- geometric isomers exhibited similar distribution profiles, prominent in the MeJA_12 and the MeSA_24 conditions.…”
Section: Resultsmentioning
confidence: 99%
“…42,66 and some studies have shown that hydroxycinnamic acids cause reduction of cell viability and apoptosis of tumour cells. 46,47 Specically, chlorogenic acids and their derivatives have been shown to be able to decrease the number of cells in phases G 0 / G 1 and increase cells in phase S. 69,70 This may explain the observation that green and light roasts caused greater increase in the S phase than did medium roast, because these compounds are degraded during roasting. Probably in dark roast, the amount of chlorogenic acids was not sufficient to have biological effects on cells.…”
Section: Effects Of Green and Roasted Coffee Extracts On Cell Viabilimentioning
confidence: 99%
“…DNA damage, and cell cycle perturbations induced by two representative gold(III) complexes in human leukemic cells with different cisplatin sensitivity [26] .This made 2P effect on the disturb DNA lead to PC3 cell cycle arrest. The effect on the S phase arrest coupled with Bcl-2 down regulation cause anti-proliferation effect to PC3 cell [27] . Melatonin was shown that indole increases neuroendocrine markers and this cause increases cell sensitivity to apoptosis induced by cytokines [28] .…”
Section: Discussionmentioning
confidence: 99%